The Low Income Tax in Iraq Causes and Treatments for the Period 2013-2016: Pajak Penghasilan Rendah di Irak: Penyebab dan Solusi untuk Periode 2013-2016 - Kareem Obayes Hassan Al-Azzawi; Mohammed Madlool Ali Al-Sultan (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Tax revenues, particularly income tax, are a fundamental component of national budgets and serve as a more sustainable funding source than volatile oil revenues or external borrowing. Specific Background: In Iraq, reliance on oil revenues has overshadowed the role of income taxes, resulting in unstable fiscal capacity and limited public service delivery. Knowledge Gap: Despite Iraq’s fiscal challenges, little research has systematically examined the relationship between income tax revenues and broader economic performance, especially GDP. Aim: This study investigates the causes of low income tax revenues in Iraq between 2003 and 2016 and evaluates their relationship with GDP growth. Results: The findings reveal that income tax contributed on average only 1% to GDP, far below comparable countries, due to excessive exemptions, weak administration, low tax awareness, and dependency on oil. Granger causality tests indicate that income tax revenues significantly influence GDP, while GDP growth also affects tax revenues. Novelty: This research provides one of the first empirical analyses of the bidirectional relationship between income tax revenues and GDP in Iraq during the post-war recovery period. Implications: The results underscore the need for comprehensive tax reforms, reduced exemptions, and improved governance to diversify Iraq’s fiscal base and enhance sustainable economic development.Highlight : Income tax revenues in Iraq remain low compared to GDP. Strong dependence on oil reduces diversification of revenues. Tax exemptions and weak administration hinder revenue growth. Keywords : Income Tax, Iraq, Public Revenues, GDP, Oil Revenues